Why Are Residents Reluctant to Consult Attending Physicians? - Otto H. Swank (Tinbergen Institute, 2009)
A physician performs two tasks: making diagnoses and determining treatments. To reduce medical error, residents are supposed to consult their supervisors when they face uncommon circumstances. However, recent research shows that residents are reluctant to do so. This paper presents a model that explains (i) which residents shy away from consulting; (ii) when residents are reluctant; (iii) the importance of protocols in the medical sector; and (iv) when consulting is a sign of strength or a sign of weakness. Furthermore, I show that encouraging residents to consult by investigating mishaps leads to another distortion: residents will give too much weight to own assessments.
Keywords: D21; D82; D83; 330; Medical error; medical decision-making; reputational concerns; consulting; Ambulante Behandlung; Konsumentenverhalten; Asymmetrische Information; Meinung; Ärzte